2019
DOI: 10.3390/ijms20020437
|View full text |Cite
|
Sign up to set email alerts
|

Lectin Sequence Distribution in QTLs from Rice (Oryza sativa) Suggest a Role in Morphological Traits and Stress Responses

Abstract: Rice (Oryza sativa) is one of the main staple crops worldwide but suffers from important yield losses due to different abiotic and biotic stresses. Analysis of quantitative trait loci (QTL) is a classical genetic method which enables the creation of more resistant cultivars but does not yield information on the genes directly involved or responsible for the desired traits. Lectins are known as proteins with diverse functions in plants. Some of them are abundant proteins in seeds and are considered as storage/d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 52 publications
0
13
0
Order By: Relevance
“…Rice (Oryza sativa) is one of the major cereal crops worldwide and it is the main food source for more than half of the human population around the world and 68% of the Asian country's population like India, Nepal, Pakistan, China, Bangladesh, Philippines, Thailand and Malaysia [1,2]. It is cultivated in around 114 countries all over the world, whereas more than 90% of crop production has been occurring in Asian countries.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rice (Oryza sativa) is one of the major cereal crops worldwide and it is the main food source for more than half of the human population around the world and 68% of the Asian country's population like India, Nepal, Pakistan, China, Bangladesh, Philippines, Thailand and Malaysia [1,2]. It is cultivated in around 114 countries all over the world, whereas more than 90% of crop production has been occurring in Asian countries.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, rice demand is increasing day by day, gradually because of population overgrowth worldwide and It is predicted that by 2050 the general agricultural production should increase by 60% to cover the food requirements. In particular, the rice demand of Asia is expected to be 70% higher within 30 years [1]. In other hand farmers are facing challenges to meet the demand of rice because of reducing fertile agricultural lands due to urbanization and to high prevalence of fungal rice diseases like rice blast and sheath blight [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…In morphological traits, 65 genes (58.6%) were found in leaf morphology QTL, whereas 30.6% and 32.4% were reported for panicle/grain and root morphology characteristics. Though, Tsaneva and colleagues reported that the QTLs for all morphological traits in Oryza sativa did not contain any lectin sequence from the families CRA and EUL [ 14 , 43 ], in grain sorghum members of the EUL and CRA-related lectins can be found in QTLs of leaf and panicle morphological traits. The CRA gene Sobic.006G044200.1 located in QTLs associated with leaf width and angel, panicle length, and root brace was reported as one of the yieldin gene group responsible for the cell wall loosening associated with assembly and degradation [ 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…The availability of full genome sequences and assemblies made it possible for the use of bioinformatics tools to correlate QTLs with the occurrence of specific genes. it was used to study the distribution of the Receptor-like cytoplasmic kinase gene family ( OsRLCKs ) within the abiotic stress QTL in rice, and examine the distribution and overrepresentation of lectin families in morphological traits and stress responses [ 13 , 14 ]. Many studies highlighted the association between lectins and QTL, for example, the MLOC_72613 gene encodes the L-type lectin domain-containing receptor kinase III which regulates water status under drought stress through the regulation of the brassinosteroid mediated pathway in barely [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, we analyzed the expression pattern of LYP genes during wheat development. Previous study showed that OsEMSA1 appeared in QTL for panicle, seeds, and sterility but not in any other QTL for morphological/physiological traits or QTL for tolerance/resistance [43]. Another study showed that OsEMSA1 involved in embryo sac development in rice [44].…”
Section: Discussionmentioning
confidence: 96%